Developing a Collaborative Inclusive Education Model for Children with Special Needs in Primary Schools: A Comparative Review of Practices in Southeast Asia - Mariyam, Siti (International Education Trend Issues, 2025)
Inclusive education has emerged as a central principle in ensuring equitable access to quality education for all children, including those with special needs (CWSN). This study employs a descriptive qualitative design based on a comparative literature review of inclusive education practices in Indonesia, Malaysia, and Thailand. Data were drawn from scholarly publications and policy documents between 2015 and 2024 retrieved from Google Scholar, ERIC, and Scopus databases. The findings reveal that inclusive education in primary schools has generally advanced through the admission of CWSN into regular classes but continues to be hindered by limited teacher competence and resource constraints. In response, this research proposes the Collaborative Inclusive Education Model (CIEM), emphasizing multi-stakeholder collaboration, differentiated instruction, and the cultivation of an inclusive school culture. The model promotes shared responsibility among teachers, special educators, parents, and the community in developing individualized learning plans that address diverse learner needs. Theoretically, CIEM reinforces humanistic education principles, while practically, it provides a framework for adaptive, participatory learning environments. The study concludes that collaborative and context-sensitive strategies are essential to advancing inclusive education reform in Southeast Asia.